Edward A. Pace: First-Generation Psychologist, Twenty-First Century Role Model - Puffer, Keith A. (Religions, 2019)
In 1891, Edward A. Pace, a Catholic priest and first-generation psychologist, commenced a career at the Catholic University of America in Washington, D.C. Amidst the daunting challenges in being a professor and researcher, particularly at a newly established university, he thrust himself into a third role, apologist. Habits related to the Monsignor's three roles have contemporary relevance for psychologically-trained Protestants; in this case study, we examine four notable practices. Dr. Pace modeled an appetence for wisdom in multiple disciplines, a keen awareness of rival worldviews, intentional ripostes to Catholic critics of scientific psychology, and last, unrelenting steadfastness to the Christian faith. To characterize the priest-psychologist, we present a brief biographical sketch and an overview of influential historical movements in the zeitgeist of the late 19th and early 20th centuries affecting his life. In addition, the aforementioned habits of Pace and applications for Protestants engaging in psychology in the 21st century are delineated.